A study on logistics management of Suzuki Bangladesh - Rancon Motorbikes Ltd. - Mobarak, Mobin Mohammed (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.